Blues in stereo : the early works of Langston Hughes, 1921-1927 - Hughes, Langston, 1902-1967 (Legacy Lit, an imprint of Hachette Books, 2024)
"Harlem Renaissance poet Langston Hughes was most well-known for his poems, novels, and plays that highlight Black American life in post-slavery America. James Mercer Langston Hughes was born on February 1, 1901, in Joplin, Missouri and began writing poetry when he moved to Lincoln, Illinois. After graduating from high school, he spent a year in Mexico followed by a year at Columbia University. During this time, he worked as an assistant cook, a launderer, and a busboy. He also traveled to Africa and Europe working as a seaman before finishing his college education at Lincoln University in Pennsylvania three years later. Setting the stage for an enduring and genre-defining career, Hughes wanted to tell the stories of his people in ways that reflected their actual culture, including their love of music, laughter, and language, alongside their suffering. He began writing short pieces in his personal notebooks before seeking a home for his resonant verse. Over the course of his four-decade career, Hughes published his first book of poetry with Knopf in 1926 as well as poems with Yale University and small, grassroots literary magazines. Today, he stands as one of the greatest literary innovators. But how did this literary giant rise to such heights? Blues in Stereo zooms in on Hughes's early work (1919-1929). National Book Award finalist Danez Smith joins as curator for this work, offering an introduction on Hughes's lyrical, evocative, and award-winning poetry and notes on the formation of his signature style and craft. Collected from libraries and little-known publications across the country, Blues in Stereo features some of Hughes's earliest undiscovered writings; the collection of his poems published in The Crisis, a monthly publication form the NAACP edited by W.E.B. DuBois from 1910-1934; and even an original unreleased play co-written with DuBois, complete with a full score. This beautifully rendered collection of Hughes's early works is sure to become a bookshelf staple"--